Restauración de imágenes en blanco y negro a través de la detección y mejoramiento de sus bordes - López Peña, Germán (2009)
The objective of this project is the restoration of images in black and white. The images restored will be black and white photographs which, because of their age or digitalization process, have diminished in quality. The restoration will be done with the detection and improvement of borders. For this Laplacian and Canny filters, along with Wavelet Haar and Sym2 filters, will be used. Through the project different images will be processed with each of the filters to determine which one produces the best visual result. The resulting images will be evaluated through a survey, to be able to determine which filter offers the desired effect. Additionally, the mean squared normalized error will be determined as well as the processing time of the filters. All of this factors will be used to choose the right filter, depending on the processing limitations of the computer that will be used.